Sex Differences in Common Sports Injuries. Issue 10 (14th March 2018) - Lin, Cindy Y.; Casey, Ellen; Herman, Daniel C.; Katz, Nicole; Tenforde, Adam S.
Abstract: Common sports injuries include bone stress injuries (BSIs), anterior cruciate ligament (ACL) injuries, and concussions. Less commonly recognized are the specific sex differences in epidemiology, risk factors, and outcomes of these conditions by sex. An understanding of these factors can improve their clinical management, from prescribing appropriate prehabilitation to guiding postinjury rehabilitation and return to play. This narrative review summarizes the sex differences in the diagnosis and management of BSIs, ACL injuries, and concussions. Although BSIs are more common in female athletes, risk factors for both sexes include prior injury and relative energy deficiency in sport (RED‐S). Risk factors in female athletes include smaller calf girth, femoral adduction, and higher rates of loading. Female athletes are also at greater risk for developing ACL injuries in high school and college, but their injury rate is similar in professional sports. Increased lateral tibial slope, smaller ACL size, and suboptimal landing mechanics are additional risk factors more often present in female athletes. Male athletes are more likely to have ACL surgery and have a higher rate of return to sport. Concussions occur more commonly in female athletes; however, female athletes are also more likely to report concussions. Male athletes more commonly sustain concussion through contact with another player. Female athletes more commonly sustain injury from contact with playing equipment. Managing post‐concussion symptoms is important, and female athletes may have prolonged symptoms. An understanding of the sex‐specific differences in these common sports injuries can help optimize their prehabilitation and rehabilitation. Level of Evidence: IV